Off-Pump and On-Pump Coronary Revascularisation in Over 70 Years Old Patients - GÖRÜR, Alper; ÖZAY, Batuhan; KETENCİ, Bülend and ORHAN, Gökçen and GÜNEY, Mehmet and DEMİRTAŞ, M. Murat and GÜRER, Onur and GÜNAY, Rafet and ÇİMEN, Serdar and SARI, Sibel (Cerrahpaşa Medical Journal, 2014)
Though perioperative outcome of beating heart surgery have been considered better than conventional methods, late results are still controversial especially in elderly patients. In this clinical trial we have compared early and late results of 71 aged cases operated either by beating or conventional methods. Preoperative risk factors of both groups were comparable except chronic obstructive pulmonary disease. In perioperative parameters, conventional group had statistically significantly longer intensive care and hospital stay days. During late follow-up period mortality rates were comparable but functional capacity of conventional group were better. Perioperative merits and late outcomes of both techniques should be evaluated for decision of operative technique.